Analgesic effect of herbal extract - Manjarrez Escamilla, Martha; González Meléndez, Rosalva; De la Garza Ramos, Myriam Angélica; Hernández Martínez, Humberto Carlos; Cruz Palma, Guillermo; Quiroga García, Miguel Ángel; Tijerina González, Liliana Zandra; Palomares Gorham, Paula Isabel; Galindo Lartigue, Carlos; Carvajal Montes de Oca, María de los Ángeles Andrea (Asian Network for Scientific Information, 2019)
Background and Objective: Regardless of the socioeconomic level and fear of dental care, most people let their dental diseases to progress until pain becomes unbearable, turning acute pain into chronic pain. This represents 40% of the causes for which people seek dental care. The objective of this study was to determine the analgesic effect of a Swedish herbal extract in an animal model. Materials and Methods: This study included 80 Mus musculus mice 4-6 weeks of age, randomly distributed into 4 groups of 20 mice. The experiment was carried out in three stages. The extract was administered orally and the response on the hot plate at 15 and 30 min was evaluated. The Turkey HSD test and a variance of analysis test were used for comparisons between groups. Results: The results in the three days were 16.60±3.81, 17.44±5.79 and 16.10±1.84 sec for the Swedish herbal extract compared to 11.51±3.84, 15.47±3.17 and 17.84±3.02 sec for meloxicam, 15 min after compound administration. In the 30min tests, the results were 16.52±5.17, 12.34±2.55 and 13.97±6.33 sec for the Swedish herbal extract compared with meloxicam which was 17.72±6.05, 17.84±5.63 and 17.38±6.33. Conclusion: The analgesic effect of the Swedish herbal extract was effective and similar to meloxicam. It is an excellent option as an alternative or complementary drug treatment.